Assessment of Bone Metastases in Patients with Prostate Cancer-A Comparison between 99mTc-Bone-Scintigraphy and [68Ga]Ga-PSMA PET/CT - Lena Thomas; Caroline Balmus; Hojjat Ahmadzadehfar; Markus Essler; Holger Strunk; Ralph A. Bundschuh (MDPI AG, 2017)
Purpose: Bone scintigraphy is the standard of reference in bone metastases in prostate cancer patients. However, new radiotracers employed in prostate-specific membrane antigen (PSMA)-ligands has led to the growing importance of PET/CT as diagnostic tool. The aim of our study was to investigate the difference between bone scan and PSMA-PET/CT for the detection of bone metastases in prostate cancer. Methods: Thirty patients with bone metastases originating from prostate cancer were examined by 99mTc-MDP bone scan and 68Ga-PSMA-PET/CT within an average of 21 days. Bone scans were analyzed visually according to the number of lesions and using the software package ExiniBONE by Exini Diagnostics. PET/CT data was analyzed visually. Numbers of detected lesions were compared for the different methods for the whole patient and for different regions. In addition, results were compared to serum prostate-specific antigen (PSA), alkaline phosphatase (ALP), bone alkaline phosphatase (bALP), pro gastrin releasing peptide (pGRP) and eastern cooperative oncology group (ECOG) performance status. Results: In the bone scans, visual and semiautomatic lesion detection showed similar results with an average of 19.4 and 17.8 detected bone lesion per patient. However, in PSMA-PET/CT, on average double the numbers of lesions (40.0) were detected. The largest differences were found in the thorax and pelvis, which can be explained by the advantages of tomographic imaging. Bland-Altman analysis showed greater differences in patients with large numbers of bone metastases. Conclusion: No significant difference was found when using semiautomatic analysis compared to visual reading for bone scans. Fewer bone metastases were detected in bone scans than in PSMA-PET/CT. However, in none of our patients would the difference have led to clinical consequences. Therefore, it seems that for patients undergoing PSMA-PET/CT, there is no need to perform additional bone scans if the appropriate PET/CT protocols are applied.